An Investigation into the Stylistic Devices Commonly used in "De Men Phieu Luu Ky" and Their English Translational Equivalents in "Diary of a Cricket" - Vu Thi Bich Ngoc
Chapter 1 Introduction; Chapter 2 Literature review and theoretical background; Chapter 3 Research design and methodology; ...